Needle-free electrospinning of nanofibrillated cellulose and graphene nanoplatelets based sustainable poly (butylene succinate) nanofibers. (September 2020) - Neibolts, N.; Platnieks, O.; Gaidukovs, S.; Barkane, A.; Thakur, V.K.; Filipova, I.; Mihai, G.; Zelca, Z.; Yamaguchi, K.; Enachescu, M.
Abstract: Sustainable materials have slowly overtaken the nanofiber research field while the tailoring of their properties and the upscaling for industrial production are some of the major challenges. We report preparation of nanofibers that are bio-based and biodegradable prepared from poly (butylene succinate) (PBS) with the incorporation of nanofibrillated cellulose (NFC) and graphene nanoplatelets (GN). NFC and GN were combined as hybrid filler, which led to the improved morphological structure for electrospun nanofibers. A needleless approach was used for solution electrospinning fabrication of nanofiber mesh structures to promote application scalability. The polymer crystallization process was examined by differential scanning calorimetry (DSC), the thermal stability was evaluated by thermal gravimetric analysis (TGA), while the extensive investigation of the nanofibers structure was carried out with scanning electron microscopy (SEM) and atomic force microscopy (AFM). NFC and GN loadings were 0.5 and 1.0 wt %; while poly (ethylene glycol) (PEG) was employed as a compatibilizer to enhance fillers' interaction within the polymer matrix. The interactions in the interface of the fillers and matrix components were studied by FTIR and Raman spectroscopies. The hybrid filler approach proved to be most suitable for consistent and high-quality nanofiber production. The obtained dense mesh-based structures could have foreseeable potential application in biomedical field like scaffolds for the tissue and bone recovery, while other applications could focus on filtration technologies and smart sensors. Graphical abstract: Image 1 Highlights: Poly(butylene succinate) composite nanofibers have been electrospun by a needleless approach using industrial pike electrode. Ability to tailor the nanofiber morphology characteristics with hybrid fillers has shown more advantages than single fillers. Broadening the potential applications for nanofibrillated cellulose and graphene.